Pengaruh Kualitas Layanan dan Citra Merek dalam Meningkatkan Kepuasan Tamu Hotel Santika - Novi Andriani; Adfiyani Fadjar; Muzakir Muzakir; Rachman Tambaru (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research aims to determine the effect of service quality and brand image on increasing guest satisfaction at Hotel Santika Palu. Methodology: The population in this study were visitors who stayed at the Hotel Santika Palu, the sampling technique was nonprobability sampling using Purposive sampling, the final sample was 90 respondents. This study used a quantitative approach method. Multiple linear regression analysis test was used in this study using the spss application version 24.0 Results: These results indicate that service quality and brand image have a positive and significant effect on increasing customer satisfaction, service quality has a positive and significant effect on increasing customer satisfaction and brand image has a positive and significant effect on increasing customer satisfaction. Thus, increasing both variables has the potential to strengthen guest satisfaction and increase their chances of returning to stay at Hotel Santika Palu in the future. Conclusion: The study concludes that service quality and brand image are critical factors in improving guest satisfaction. Strengthening these elements can enhance guest experiences and loyalty, which is essential for maintaining competitive advantage in the hospitality industry. Limitations: The limitation of this research is that it was only conducted at one hotel, namely Hotel Santika Palu, so the results cannot be generalized to other hotels with different characteristics or in different locations. Contribution: This research has implications for the importance of improving service quality and strengthening brand image as the main strategy in efforts to increase guest satisfaction.